Exploring the bidirectional relationships between night eating, loss of control eating, and sleep quality in Chinese adolescents: A four‐wave cross‐lagged study. Issue 10 (13th August 2022) - Weng, Hongbin; Barnhart, Wesley R.; Cheng, Yawei; Chen, Gui; Cui, Tianxiang; Lu, Tom; He, Jinbo
Abstract: Objective: This study examined the bidirectional relationships between sleep quality, loss of control (LOC) eating, and night eating in Chinese adolescents using longitudinal data over an 18‐month study period. Method: Four‐waves of data measurement (Waves 1–4), at 6‐month intervals, were conducted with 2566 adolescents aged 11–17 years at baseline. A set of questionnaires were used to assess night eating, LOC eating, and sleep quality at each wave of data collection. Cross‐lagged models were applied to analyze the bidirectional relationships between night eating, LOC eating, and sleep quality. Results: Results indicated that higher night eating scores consistently predicted poorer sleep quality and higher LOC eating scores at Waves 1, 2, and 3. Furthermore, poorer sleep quality predicted higher night eating scores at Wave 1 and Wave 3, and higher LOC eating scores predicted higher night eating scores at Wave 1 and Wave 2. Discussion: These findings highlight that night eating, LOC eating, and sleep quality were interrelated across time in Chinese adolescents. Improving sleep quality and reducing LOC eating might be promising in the prevention of night eating in adolescents. Similarly, reducing night eating might be promising in improving sleep quality and reducing LOC eating in adolescents. Public Significance: This study explored the bidirectional relationship between night eating, LOC eating, and sleep quality in Chinese adolescents using cross‐lagged models. Findings indicate bidirectional relationships between these variables and highlight the potential utility in incorporating sleep, LOC eating, and night eating interventions in eating pathology prevention designs for adolescents.